Front Cover: One Way Traffic: Base‐to‐Backbone Hole Transfer in Nucleoside Phosphorodithioate (Chem. Eur. J. 43/2020). Issue 43 (22nd June 2020) - Kaczmarek, Renata; Ward, Samuel; Debnath, Dipra; Jacobs, Taisiya; Stark, Alexander D.; Korczyński, Dariusz; Kumar, Anil; Sevilla, Michael D.; Denisov, Sergey A.; Shcherbakov, Viacheslav; Pernot, Pascal; Mostafavi, Mehran; et al.
Abstract : The direction of hole transfer (unpaired spin) in the DNA‐component, occurring between base and modified phosphate, is depicted in the cover artwork. This process critically determines the DNA‐backbone damage. In one‐electron oxidized phosphorodithioate nucleotide, the hole is initially localized on guanine base as a cation radical (Gua .+ ). Next, via base‐to‐backbone hole transfer, the hole appears on phosphorodithioate as dithiyl radical. Cover art designed by Ariela Kaspi‐Kaneti, with contribution from Aditya Paul. More information can be found in the Full Paper by R. Dembinski, A. Adhikary, et al. on page 9495 .